Pengaruh Konsentrasi Carnauba Wax Sebagai Oleogelator Terhadap Oil Binding Capacity Oleogel Minyak Sawit Merah - Agnes Vanessa; I Wayan Rai Widarta; I Gusti Ayu Kadek Diah Puspawati (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Oleogel is oil structured into a semi-solid system, in which the hydrophobic liquid phase is entrapped within a three-dimensional matrix. One of the oils that can be used to produce oleogel is red palm oil (RPO). The most important factors in oleogel production are the concentration and type of oleogelator added, particularly in determining the oil binding capacity (OBC) of the oleogel. This study aimed to determine the effect of Carnauba wax (CW) concentration on the OBC of red palm oil oleogel and to identify the optimum concentration that yields an oleogel with 100% OBC, along with desirable physical characteristics and carotenoid content. The experiment was conducted using a Completely Randomized Design with five levels of CW concentration (5%, 7%, 9%, 11%, and 13%), each replicated three times, resulting in 15 experimental units. The parameters observed included OBC, carotenoid content, hardness, and color intensity (L*, a*, b* values, and descriptive color). The data obtained were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT). The results showed that increasing CW concentration significantly affected the OBC and hardness of the oleogel, altered its color, and reduced carotenoid content. The oleogel prepared with 11% CW produced the best characteristics, achieving an OBC of 100%, hardness of 1.61 N, carotenoid content of 225.97 mg/kg, L* value of 33.02, a* value of 28.05, and b* value of 43.27, with an olive sienna color.